2017
DOI: 10.5194/acp-17-10919-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term O<sub>3</sub>–precursor relationships in Hong Kong: field observation and model simulation

Abstract: Abstract. Over the past 10 years (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), ground-level O 3 in Hong Kong has consistently increased in all seasons except winter, despite the yearly reduction of its precursors, i.e. nitrogen oxides (NO x = NO + NO 2 ), total volatile organic compounds (TVOCs), and carbon monoxide (CO). To explain the contradictory phenomena, an observation-based box model (OBM) coupled with CB05 mechanism was applied in order to understand the influence of both locally produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 77 publications
10
42
0
Order By: Relevance
“…Figure 3 illustrates surface wind fields and air movement 2 days (i.e., 20-21 September) before the occurrence of Usagi as an example. It can be seen that when Usagi approached southeastern area of Hong Kong, it led to weak northeasterly and later northwesterly winds which potentially delivered O 3 and its precursors from highly polluted inland PRD region to the sampling sites (Yin, 2004;Wei et al, 2016;Wang et al, 2017). The wind speed was lower than 4 m s −1 at the sampling sites and in their surrounding area on 20 September (Fig.…”
Section: Tropical Cyclonesmentioning
confidence: 94%
See 3 more Smart Citations
“…Figure 3 illustrates surface wind fields and air movement 2 days (i.e., 20-21 September) before the occurrence of Usagi as an example. It can be seen that when Usagi approached southeastern area of Hong Kong, it led to weak northeasterly and later northwesterly winds which potentially delivered O 3 and its precursors from highly polluted inland PRD region to the sampling sites (Yin, 2004;Wei et al, 2016;Wang et al, 2017). The wind speed was lower than 4 m s −1 at the sampling sites and in their surrounding area on 20 September (Fig.…”
Section: Tropical Cyclonesmentioning
confidence: 94%
“…However, increasing studies showed that surface O 3 was elevated rapidly in East Asia in the last decade (Ding et al, 2008;Xu et al, 2008;Parrish et al, 2012;Xue et al, 2014;Zhang et al, 2014;Sun et al, 2016;Lin et al, 2017;Wang et al, 2017). For example, the observational data revealed that regional O 3 concentrations increased at a rate of 0.86 ppbv yr −1 in Pearl River Delta (PRD) from 2006 to 2011 (Li et al, 2014), at a rate of 0.56 ppbv yr −1 in Hong Kong from 2005 to 2014 (Wang et al, 2017), and even at a rate of 1.7-2.1 ppbv yr −1 (summertime only) at Mount Tai in central eastern China (Sun et al, 2016).…”
Section: H Wang Et Al: Ozone Pollution Around a Coastal Region Of Smentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study in Hong Kong investigated associations between O 3 and its precursors, i.e. NO X and 21 NMHCs during 2005-2014 (Wang et al, 2017). O 3 concentrations in Hong Kong increased (0.56 ppb/year, p<0.01) while NOx decreased (-0.71 ppb/year, p<0.01).…”
Section: Introductionmentioning
confidence: 99%